From the center of pressure to the center of gravity, a new algorithm for a step forward in stabilometry - Gagey, Bernard; Bourdeaux, Olivier; Gagey, Pierre-Marie (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: For more than thirty years, in clinical stabilometry, we have been using the center of pressure (CoP) to calculate stabilometric parameters. That was a mistake because the CoP signal comprises two series of information, one on the position of the center of gravity (CoG), and the other on the acceleration of the CoG. Objective: A step forward must be taken in order to separate these variables clearly using the CoG instead of the CoP to calculate stabilometric parameters. A lot of methods have been proposed to obtain the CoG from the CoP, yet none of them is used. We present a new algorithm for the same purpose. Method: A new mathematical way for solving the differential equation of DA Winter is proposed, which can use the "edge effects" due to known boundary conditions of the variables. Result: Solving the Winter’s equation has two interests: Clinicians may think about what is observed through a model, and inter-subjects comparisons are better thanks to Winter’s coefficient. Conclusion: During its next session, the international Committee for standardization of clinical stabilometry must choose one method to obtain the CoG from the CoP, before this choice is made, this new method must be known, well known and well understood because it could be the best choice.